Pendampingan Model Pembelajaran Inovatif di Sekolah Dasar Kecamatan Simeulue Timur Kabupaten Simeulue - Afriani; Adi Saleh; Azizah; Wolly Mistiar; Saiful Marhaban; Zainuddin (Yayasan Kawanad, 2022)
This mentoring program aims to improve the ability of teachers in integrating innovative learning models in learning in elementary school (SD) 1 Kecamatan Simeulue Timeur Aceh. The ability to integrate innovative learning models in learning requires specific skills in their application. Responding to that, done by the teachers to be able to integrate innovative learning model effectively according to the demand of learning in elementary school. Methods of assistance are conducted through several stages of activity, including: preparation, implementation, evaluation and reflection, and follow-up. Outcomes generated through the mentoring program include: an innovative learning model guidebook in elementary school, teacher model of integrating innovative learning model, and scientific article published in ISSN online journal. The results of the devotion program indicate that the increasing ability of teachers in integrating innovative learning models in learning in SD1 Simeulue Timur Sub-district Simeulue. Thus, the assistance performed has been run effectively and in accordance with the expected results.